The Role of Predictors in the Development of Arrhythmia and Cardiac Conduction Disorders in Highly Qualified Football Players (Global Journal of Medical Research, 2023)
Abstract not found
Keywords: heart rhythm disturbances; physical performance in athletes; maximum oxygen consumption; adaptation to physical activity